Evaluating the safety and efficacy of regional citrate compared to systemic heparin as anticoagulation for continuous renal replacement therapy in critically ill patients: A service evaluation following a change in practice. (August 2017) - Borg, Roberta; Ugboma, Debra; Walker, Dawn-Marie; Partridge, Richard
Following the implementation of citrate anticoagulation for continuous renal replacement therapy, we evaluate its first year of use and compare it to the previously used heparin, to assess whether our patients benefit from the recently reported advantages of citrate. We retrospectively analysed 2 years of data to compare the safety and efficacy of citrate versus heparin. The results have shown that 43 patients received continuous renal replacement therapy with heparin, 37 patients with citrate. We found no significant difference in metabolic control of pH, urea and creatinine after 72 h. Filters anticoagulated with citrate had significantly longer median lifespan (33 h vs 17 h; p  = 0.001), shorter downtime (0 h vs 5 h; p  = 0.015) and less filter sets per patient day (0.37 vs 0.67; p  = 0.002). Filters anticoagulated with heparin were commonly interrupted due to clotting (50% vs 16.4%), whereas filters anticoagulated with citrate were often stopped electively (53.4% vs 24.6%). Patients on heparin filters had significantly higher APPTs, some at potentially dangerous levels (>180 s), whilst patients on citrate filters had significantly higher levels of bicarbonate. Therefore, we conclude that citrate is superior in terms of safety and efficacy, with longer filter lifespan. It has become our first line anticoagulant for continuous renal replacement therapy.